Sub Branch Financial Performance Analysis: A Study on Islami Bank Bangladesh Limited (IBBL) - Sikder, Md. Sajeeb (Asian Accounting and Auditing Advancement, 2022)
The banking sector is an important sector of an economy of a country, so it is necessary to monitor and evaluate its performance. This paper examines the performance of Islamic banking in Bangladesh, particularly the experience of the Sub-branch of Islami Bank Bangladesh Limited. The article further explores expertise on the sub-branch sector’s domestic and global challenges. The performance evaluation methodology is used to ascertain profit maximization objectives, capital structure, and liquidity ratios. We used the bank’s financial data from 2017 to 2021 and observed that all indicators’ trends are positive. The ability, efficiency, and number of products of the Sub-branch of Islami Bank Bangladesh Limited are increasing gradually. For example, the investment of the Sub-branch of Islami Bank Bangladesh Limited is mainly on a short-term basis which is generally similar to other Islamic Sub-branch in Bangladesh. Moreover, Islamic banks are facing some difficulties in their operations, especially for the non-shariah structure of their stakeholders. This study suggests that the Sub-branch of Islami banks of Bangladesh should increase the Islamic capital market, Islamic financial instruments, and proper zakat distribution and employment opportunities for the betterment of society.